2014
DOI: 10.1530/erc-13-0529
|View full text |Cite
|
Sign up to set email alerts
|

Differential roles of PPARγ vs TR4 in prostate cancer and metabolic diseases

Abstract: Peroxisome proliferator-activated receptor g (PPARg, NR1C3) and testicular receptor 4 nuclear receptor (TR4, NR2C2) are two members of the nuclear receptor (NR) superfamily that can be activated by several similar ligands/activators including polyunsaturated fatty acid metabolites, such as 13-hydroxyoctadecadienoic acid and 15-hydroxyeicosatetraenoic acid, as well as some anti-diabetic drugs such as thiazolidinediones (TZDs). However, the consequences of the transactivation of these ligands/activators via thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 172 publications
0
17
0
Order By: Relevance
“…; Liu et al . ). Recent studies have reported that in addition to their cognate ligands, activities of these receptors could be regulated by a variety of lipophilic molecules, including fatty acids and various environmental chemicals (King‐Jones & Thummel ).…”
Section: Discussionmentioning
confidence: 97%
“…; Liu et al . ). Recent studies have reported that in addition to their cognate ligands, activities of these receptors could be regulated by a variety of lipophilic molecules, including fatty acids and various environmental chemicals (King‐Jones & Thummel ).…”
Section: Discussionmentioning
confidence: 97%
“…Because both TR4 and PPARγ have high affinities for DR1 elements, target genes of these two receptors are considerably overlapped (Liu et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…this study, we showed that PPARγ transcriptional activity is significantly stimulated at 400 μM PYR, at which TR4 activity could not be enhanced, clearly showing that TR4 and PPARγ can respond to PYR at different concentrations. Because both TR4 and PPARγ have high affinities for DR1 elements, target genes of these two receptors are considerably overlapped (Liu et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Xie et al [23] found PPAR ligands/activators such as the PUFA metabolites, 15-HETE and 13-HODE, could trans-activate TR4, and some TZDs could also trans-activate TR4 to modulate its down-stream target CD36 activity during foam cell formation/atherosclerosis [39]. …”
Section: Discussionmentioning
confidence: 99%